ANALISIS KINERJA FINANSIAL DAN NON FINANSIAL PADA ANEKA FOOD - Marlin Domi Taruk Lembang; Longginus Gelatan (JURNAL ULET (Utility, Earning and Tax), 2022)
This study aims to determine the non-financial and financial performance of the Aneka Food. The method used is descriptive method. This analysis begins by collecting data from the Aneka Food, then processing the data that has been collected by analyzing the company's performance using the balance scorecard method. The results of this study indicate that the non-financial performance of the Aneka Food is classified as poor, while the financial performance of the Aneka Food is classified as good.